A general magnitude system in human adults: Evidence from a subliminal priming paradigm. (August 2016) - Lourenco, Stella F.; Ayzenberg, Vladislav; Lyu, Jennifer
Abstract: Despite general agreement that number and other magnitudes share analog format, there is disagreement about the extent to which representations of numerical and non-numerical magnitude recruit common cognitive and neural resources. Cross-dimensional interactions between number and other magnitudes on Stroop-like tasks have been taken as evidence for integration across magnitudes, but such effects are subject to alternative interpretations that allow for differentiated representations. Here we use a subliminal priming paradigm to test for interactions between different magnitudes (number and area) when one magnitude is not consciously detectable. Across two experiments, we first provide evidence for the feasibility of this paradigm by demonstrating that transfer occurs within the dimension of number; that is, symbolic numerals (Arabic digits) that were subliminally primed affected judgments of non-symbolic numerosities in target displays. Crucially, we also found transfer across magnitudes—from subliminally primed numerals to target displays of cumulative surface area whether participants made an ordinal judgment (i.e., "which array is larger in area?") or judged whether two arrays were the same or different in area. These findings suggest that representations of number and area are not fully differentiated. Moreover, they provide unique support for a general magnitude system that includes direct connections, or overlap, between the neural codes for numerical and non-numerical magnitudes.